If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 = 3x + 21 Reorder the terms: 12 + 6x = 3x + 21 Reorder the terms: 12 + 6x = 21 + 3x Solving 12 + 6x = 21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 6x + -3x = 21 + 3x + -3x Combine like terms: 6x + -3x = 3x 12 + 3x = 21 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + 3x = 21 + 0 12 + 3x = 21 Add '-12' to each side of the equation. 12 + -12 + 3x = 21 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 21 + -12 3x = 21 + -12 Combine like terms: 21 + -12 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| (-8)(-4)(0)= | | 4x=-25-6x | | 1.4+(0.9)= | | x-2/4=5 | | y^3+4y^2+6y+4=0 | | 3(5x-10)=20x | | 2x=-7x+18 | | 12y-18x=18 | | 10n=7n+7+2n | | 9x-(3*7)=6 | | 5000x=250+20x | | y^2+14y+27=0 | | 7-2(f+3)=2(4-3f) | | -2x+7=28 | | 3(8-5)-3(16+12)= | | X-4-3x=-2x+5-1 | | 4x-21+7x-3=9x-11+3x | | 6u^2-u-1=0 | | 6p+13=31 | | 3x+12y=51 | | 5m+12+2m=2m+18-5 | | -4.9+x=11.3 | | (6x-11)/2x | | 4a-(a-2)=19+3a | | -12x+3x-202=59 | | 6+4a=16+2a | | 20=5y/7 | | -(5x-5)= | | -113+5x+10x=97 | | 5-(h+3)=-1+2(h-3) | | 5-2x=x+9 | | 15-18=r |